The Platonic Meta-Imports in Luigi Pirandello’s Six Characters in Search of an Author - Abd Al-Ameer, Zainab Hasoon (Al-Adab Journal, 2015)
Though Plato’s aim in the seventh and tenth books of The Republic was to expose a false world of shadows that must be abandoned for the real world, still his influence on drama, ancient and modern, and its theory is immensely there. His cave parable, itself a dramatic rendition of ideas, is perhaps the first well established theory of drama and dramaturgy. What is more, the drama and theory of the cave has become the medium for what is called metatheatre. Metatheatre turns out to be a marking of modernism in art and literature, and complex phenomenon that addresses issues related to philosophy, communication, epistemology, and aesthetic. Metatheatre is full of ideas comparable to Plato’s which give the audience the mutations of truth when they should look for answers themselves. The aim of this paper is to approach Luigi Pirandello’s work which is replete with the above Platonic philosophical and dramatic meta-imports. His drama entices the audience to open their eyes to realities through showing them something that is completely made up. In Six Characters in Search of an Author, he tries to re-enact the play of the shadows of Plato’s cave. He explores the nature of theatrical processes by making his character escape from life into form and from form into reality